Pre-Exposure Prophylaxis (PrEP) Utilization in the College-Health Setting - Hall, Christina (My University, 2024)
Pre-exposure prophylaxis (PrEP) medication was introduced in 2012 to reduce the chance of acquiring HIV via sex by 99 percent (Centers for Disease Control and Prevention [CDC], 2022). Despite having a prevention method with such promising results, underutilization continues to be a concern in North Carolina. The CDC stated that 32,490 people in North Carolina could have benefitted from PrEP, but only 5,288 were prescribed the medication (CDC, 2022a). This quality improvement project aimed to evaluate the beliefs and habits of providers at a university in North Carolina regarding PrEP and, thus, their medication utilization. Providers in this setting serve as gatekeepers in disseminating PrEP but face institutional barriers. Continued education and evaluation of their attitudes and comfort with prescribing PrEP can allow these concerns to be addressed, making providers more likely to utilize this means of HIV prevention.
Keywords: HIV, PrEP, college-health, prevention, utilization